High sensitivity fiber optic angular displacement sensor and its application for detection of ultrasound - Salvi Sakamoto, Joao Marcos; Kitano, Claudio [UNESP]; Pacheco, Gefeson Mendes; Tittmann, Bernhard Rainer (Optical Soc Amer, 2012)
In this paper, we report on the development of an intensity-modulated fiber-optic sensor for angular displacement measurement. This sensor was designed to present high sensitivity, linear response, and wide bandwidth and, furthermore, to be simple and low cost. The sensor comprises two optical fibers, a positive lens, a reflective surface, an optical source, and a photodetector. A mathematical model was developed to determine and simulate the static characteristic curve of the sensor and to compare different sensor configurations regarding the core radii of the optical fibers. The simulation results showed that the sensor configurations tested are highly sensitive to small angle variation (in the range of microradians) with nonlinearity less than or equal to 1%. The normalized sensitivity ranges from (0.25 x V-max) to (2.40 x V-max) mV/mu rad (where V-max is the peak voltage of the static characteristic curve), and the linear range is from 194 to 1840 mu rad. The unnormalized sensitivity for a reflective surface with reflectivity of 100% was measured as 7.7 mV/mu rad. The simulations were compared with experimental results to validate the mathematical model and to define the most suitable configuration for ultrasonic detection. The sensor was tested on the characterization of a piezoelectric transducer and as part of a laser ultrasonics setup. The velocities of the longitudinal, shear, and surface waves were measured on aluminum samples as 6.43, 3.17, and 2.96 mm/mu s, respectively, with an error smaller than 1.3%. The sensor, an alternative to piezoelectric or interferometric detectors, proved to be suitable for detection of ultrasonic waves and to perform time-of-flight measurements and nondestructive inspection. (C) 2012 Optical Society of America